The Cambridge handbook of personality psychology - Corr, Philip J. ;Matthews, Gerald (Cambridge, United Kingdom : Cambridge University Press, 2020)
Firstly, and most importantly, chapters are longer, more detailed and pitched at a higher level, which will better meet the needs of graduate students, researchers, and more seasoned academics. Secondly, there is now a more even and adequate coverage of the whole of personality psychology - not only compared to the first edition but, we believe, to similar handbooks on the market. Thirdly, the first edition had separate chapters on a number of psychopathological disorders; for conceptual depth and clarity, the second edition has fewer chapters of a more integrative and comprehensive character.
General Introduction Philip J. Corr and Gerald Matthews -- Part I. Foundational Issues: History and Approaches to Personality -- Part II. Description and Measurement: How Personality Is Studied -- Part III. Development, Health and Change: Life Span and Health Outcomes -- Part IV. Biological Perspectives: Evolution, Genetics and Neuroscience of Personality -- Part V. Cognitive and Motivational Perspectives: Dynamic Processes of Personality -- Part VI. Social and Cultural Processes: Personality at the Intersection of Society -- Part VII. Applications of Personality Psychology: Personality Traits and Processes in Action -- Index.
Includes index.
Keywords: PERSONALITY